Sexual dimorphism related to growth in climbing perch Anabas testudineus - Hidayat, Rahmat; Carman, Odang; Alimuddin, , (Jurnal Akuakultur Indonesia, 2016)
ABSTRCT The phenomenon that often occurs in climbing perch culture (Anabas testudineus, Bloch) is a significant size difference between individuals of male and female those lead to high variation in culture yields. In addition to genetic factors, the difference possibly reflects the sexual dimorphism in this fish; female grows faster than male. This research was conducted to examine sexual dimorphism related to growth quantitatively. Sixty individuals of 45-days old juvenile derived from mating of five pairs broods were randomly picked up and reared individually in 20×20×100 cm3 net cages for 135 days. Fish were fed on commercial feed (30% protein) three times a day at 10% feeding rate. Body weight and body length were individually recorded every 15 days, sex was determined at the end of the experiment by surgering the fish and gonad was weighed to calculate gonadosomatic index (GSI). The results showed that growth and specific growth rate of female were 1.17 and 1.48 fold respectively higher than male. This result indicates that female monosex culture of climbing perch is highly promising. Keyword: dimorphism, growth, climbing perch, Anabas testudineus  ABSTRAK Salah satu fenomena yang sering dijumpai dalam budidaya ikan papuyu (Anabas testudineus, Bloch) adalah perbedaan ukuran yang mencolok antara individu jantan dan betina yang menyebabkan hasil panen ikan sangat bervariasi. Selain faktor genetik, perbedaan ini diduga disebabkan oleh adanya dimorfisme seksual terkait pertumbuhan. Penelitian ini dilakukan untuk menguji dimorfisme seksual terkait dengan pertumbuhan ikan papuyu secara kuantitatif. Benih ikan umur 45 hari hasil pemijahan lima pasang induk diambil secara acak sebanyak 60 ekor dan dipelihara selama 135 hari secara individu di dalam 60 unit hapa (20×20×100 cm3). Ikan diberi pakan komersial (protein 30%) tiga kali sehari sebanyak 10% bobot tubuh. Bobot dan panjang semua ikan dicatat setiap 15 hari sekali, jenis kelamin ditentukan di akhir penelitian dengan cara membedah, mengamati gonad, dan menimbangnya untuk menentukan indeks gonadosomatik (IGS). Hasil penelitian membuktikan adanya dimorfisme seksual terkait pertumbuhan pada ikan papuyu; pertumbuhan bobot mutlak dan laju pertumbuhan bobot harian ikan betina masing-masing 1,48 kali dan 1,17 kali lebih tinggi dibandingkan dengan ikan jantan. Hasil penelitian ini mengindikasikan bahwa pengembangan budidaya ikan papuyu monoseks betina prospektif untuk dilakukan. Kata kunci: dimorfisme, pertumbuhan, papuyu, Anabas testudineus